História[s] da formação inicial de professores que ensinam matemática no pós-pandemia: um estudo em educação comparada (Brasil-Portugal) - Garcia, Mariany Fonseca (Universidade Federal de São Carlos, 2026)
This dissertation presents the final results of a research project, funded by the São Paulo Research Foundation (FAPESP), developed within the scope of the "School Education: Critical Theories and Practices" line of research of the Postgraduate Program in Education at the Federal University of São Carlos (PPGE/UFSCar). Its general objective was to understand, through Oral History, the perspectives of teacher educators in Mathematics disciplines in undergraduate courses in Pedagogy (Brazil) and Education (Portugal) regarding the implications of remote teaching for pedagogical practice in the subjects they teach upon returning to in-person teaching in the post-pandemic period. Initially, we mapped theses and dissertations in the Brazilian Digital Library of Theses and Dissertations (BDTD), the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel (CAPES), and the repositories of all Portuguese universities that offer doctoral programs in Education, in order to find works that discuss mathematical training and the teaching of mathematics in courses that train teachers for the beginning of schooling. The results pointed to the predominance of Brazilian research regarding remote teaching and a limited attempt to understand how mathematics was taught during this period, while in Portugal, there was an absence of studies on teacher training during remote teaching. Therefore, we highlight the need to deepen studies that contribute to this perspective and highlight the potential of this master's research by conducting a comparative study in Education, which seeks to understand the impact of remote teaching in both contexts. To deepen our understanding of the area, we used, in our theoretical framework, authors who discuss teacher training and mathematics subjects in undergraduate Pedagogy courses in Brazil and undergraduate Basic Education courses in Portugal. In our methodology, which uses a qualitative approach, we rely on Comparative Education as an epistemic perspective, with data production and analysis through Oral History. To this end, we interviewed one teacher from the Northeast region and one teacher from the North region of Brazil, and three teachers working in Higher Education Institutions, located in Lisbon, Setúbal, and Santarém. The interviews with the Brazilian teacher educators were conducted remotely via Google Meet, while the interviews with the Portuguese teachers were conducted in person, through a Research Internship Abroad grant awarded by the São Paulo Research Foundation (BEPE/FAPESP). The results pointed to changes in teachers' pedagogical practices after the pandemic, due to the influence of remote teaching. In Brazil, the possibility of conducting some classes and meetings remotely and the addition of new digital resources to face-to-face meetings stand out. In Portugal, there was a greater exploration of technologies, especially with regard to Geometry, aligning physical and digital resources in a new dynamic of teacher training.
History of initial teacher training for those who teach mathematics in the post-pandemic period: a comparative education study (Brazil-Portugal)
Keywords: Formação de professores; Ensino remoto; História Oral; Educação Comparada; Matemática; Teacher training; Remote teaching; Oral History; Comparative Education; Mathematics; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade